The Relationship of Wheat Flour Mix with Maizena and Sodium Carbonate to the Quality of Crispy Potatoes - Rahma Wahyuni Hsbn (Contributions of Central Research Institute for Agriculture, 2022)
The aim of this research was to find the effect of mixture grist flour and corn starch with sodium carbonate on the quality of potatoes crispy. The research had been performed using completely randomized design (CRD) with 2 factors, i.e: sum of grist flour and corn starch (3:1) (C) (25%, 30%, 35%, and 40%) and percentage of sodium carbonate (P) (0.10%, 0.15%, 0.20% and 0.25%). Parameters analysed were lipid content (%), free fatty acid (%), water content (%), and organoleptic values (colour, taste, and crispisity). The result showed that sum mixture of grist flour and corn starch had highly significant effect on free fatty acid, water content, organoleptic values (colour, taste and crispisity) and had no significant effect on lipid content. Percentage of sodium carbonate had highly significant effect on free fatty acid and organoleptic value of crispisity, had significant effect on water content, and had no significant effect on lipid content and organoleptic values (colour and taste). Interaction of sum mixture grist and corn starch with percentage of sodium carbonate had significant effect on free fatty acid and water content and had no siginifant effect on lipid content and organoleptic values (colour, taste,and crispisity). To yield crispy potatoes which have crispisity and taste delicious with using the sum of mixture grist and corn starch 25%, and sodium carbonate 40%.